Pregnancy outcome after pharmacological treatment of adenomyosis of the external myometrium: case report: Pregnancy with adenomyosis - Wang, Xinyue; Shao, Xiaoguang; Lan, Xiaohan; Zhang, Jie (Serican Journal of Medicine, 2024)
Adenomyosis is the implantation of active endometrial tissue outside the uterine cavity and it is one of the common diseases that cause infertility in women. Adenomyosis can be classified into that of the internal and external myometrium depending on the location of the lesion. The external adenomyosis in this article means the lesion is located in the outer shell of the uterus, which is separated from the intact junction zone(JZ), and there are served healthy muscular structures between the adenomyosis and the JZ. And the internal adenomyosis means that in Magnetic Resonance Imaging (MRI), the lesions develops in direct connection to the thickened JZ, and the adenomyosis are preserved inside the healthy muscular structure.Although the gold standard for the diagnosis of adenomyosis is postoperative pathology, several studies propose that transvaginal ultrasound(TVUS) and MRI can be used as preoperative diagnostic tools. Comparing with TVUS, 3D-TVUS can display uterine cavity more clearly besides areas of outer involment. And MRI can confirm the status of the uterine myometrium further and classify the adenomyosis leision. Besides the above two imaging examinations, CA-125 is an also important factor for assessing condition and change of this disease.The internal and external myometrium of this disease should be considered as two different entitles and their treatment ideas should be distinct. Particularly, adenomyosis with infertility should be received comprehensive evaluation(3D-TVUS+MRI+CA125) and appropriate pregnancy planning.